Effect of a primary care management intervention on mental-health-related quality of life among survivors of sepsis: a randomized clinical trial - Schmidt, Konrad; Wensing, Michel (The journal of the American Medical Association, 2016)
Importance: Sepsis survivors face long-term sequelae which diminish health-related quality of life (HRQoL) and result in increased care needs in the primary care setting as medication, physiotherapy or mental health care. Objective: To examine if a primary care-based intervention improves mental HRQoL. Design, Setting and Participants: A randomized clinical trial was conducted between February 2011 and December 2014. 291 patients ≥18 years who survived sepsis (including septic shock) were recruited from nine intensive care units (ICU) across Germany. Intervention: Participants were randomized to usual care (n=143) or to a 12-month intervention (n=148). Usual care was provided by their primary care physician (PCP) and included periodic contacts, referrals to specialists and prescription of medication and/or other treatment. The intervention additionally included PCP and patient training, case management provided by trained nurses and clinical decision support for PCPs by consulting physicians. Main outcome: The primary outcome was change in mental HRQoL between ICU discharge and six months post-ICU using the Mental Component Summary (MCS) of the Short-Form Health Survey 36 (SF-36; range 0-100; higher ratings indicating lower impairment, minimal clinically important difference five score points). Results: The mean age of the 291 patients was 61.6 years (SD 14.4), 66.2% (n=192) were male, and 84.4% (n=244) required mechanical ventilation during their ICU stay (median 12 days, range 0-134). At six and 12 months post-ICU, 75.3% (n=219, 112 intervention, 107 control) and 69.4% (n=202, 107 intervention, 95 control) completed follow-up, respectively. Overall mortality was 13.7% at six months (40 deaths, 21 intervention, 19 control) and 18.2% at 12 months (53 deaths, 27 intervention, 26 control). Among intervention group patients, 104 (70.3%) received the intervention at high levels of integrity. There was neither a significant difference in change of MCS scores (intervention group baseline, mean=49.1, six months=52.9, change=3.79 score points (95%CI 1.05; 6.54) vs. control group baseline, mean =49.3, six months=51.0, change=1.64 score points (95%CI -1.22; 4.51) mean treatment effect=2.15 (95%CI -1.79; 6.09); p=0.28), nor in PCP care delivered between both groups. Conclusions and relevance: Among sepsis survivors, a primary-care-focused team-based intervention did not improve mental HRQoL or impact PCP care compared with usual care. Trial Registration: ISRCTN registry; http://www.isrctn.com/ISRCTN61744782